The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ctm2.802
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the quality of SARS‐CoV‐2 specific T‐cell response associated with disease severity, immune memory and heterologous response

Alberto Pérez‐Gómez,
Carmen Gasca‐Capote,
Joana Vitallé
et al.

Abstract: SARS-CoV-2 specific T-cell response has been associated with disease severity, immune memory and heterologous response to endemic coronaviruses. However, an integrative approach combining a comprehensive analysis of the quality of SARS-CoV-2 specific T-cell response with antibody levels in these three scenarios is needed. In the present study, we found that, in acute infection, while mild disease was associated with high T-cell polyfunctionality biased to IL-2 production and inversely correlated with anti-S Ig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…Our results also showed that Clec9A-RBD single dose immunization induced a potent and sustained antigen-specific poly-functional T H 1 cellular response, consistent with our previous studies that targeted antigens to Clec9A-expressing cDC1 [16, 42]. Poly-functional T cells have been proposed to represent a correlate of protection in other infectious diseases such as dengue and this feature is applicable towards COVID-19 as well [43-45]. Furthermore, Clec9A-RBD was able to elicit robust RBD-specific T cell memory that could be recalled 6-12 months post-immunization.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also showed that Clec9A-RBD single dose immunization induced a potent and sustained antigen-specific poly-functional T H 1 cellular response, consistent with our previous studies that targeted antigens to Clec9A-expressing cDC1 [16, 42]. Poly-functional T cells have been proposed to represent a correlate of protection in other infectious diseases such as dengue and this feature is applicable towards COVID-19 as well [43-45]. Furthermore, Clec9A-RBD was able to elicit robust RBD-specific T cell memory that could be recalled 6-12 months post-immunization.…”
Section: Discussionsupporting
confidence: 89%
“…These SARS‐CoV‐2 pools were made broadly available to the scientific community by distribution to over 110 laboratories in four different continents and were utilized in a large number of studies, resulting thus far in over 80 publications (Ansari et al., 2021; Ansari et al., 2022; Apostolidis et al., 2021; Arunachalam et al., 2022; Banki et al., 2022; Bhuiyan et al., 2022; Blixt et al., 2022; Boland et al., 2022; Bosteels et al., 2022; Bowen, Addetia, et al., 2022; Bowen, Park, et al., 2022; Brasu et al., 2022; Bueno et al., 2022; Cheon et al., 2021; Chiuppesi et al., 2022; Costa et al., 2022; da Silva Antunes, Pallikkuth, et al., 2021; Dan et al., 2021; Dentone et al., 2022; Galvez et al., 2022; Gao, Cai, Grifoni, et al., 2022; Gao, Cai, Wullimann, et al., 2022; Garcia‐Valtanen et al., 2022; Gazzinelli‐Guimaraes et al., 2022; Geers et al., 2023; GeurtsvanKessel et al., 2022; Goel et al., 2021; Grifoni et al., 2021; Grifoni, Sidney, et al., 2020; Grifoni, Weiskopf, et al., 2020; Hassan et al., 2020; He et al., 2022; Hsieh et al., 2022; Jin et al., 2021; Keeton et al., 2021; Keeton et al., 2022; Keeton et al., 2023; Lederer et al., 2022; Madelon, Heikkila, et al., 2022; Madelon, Lauper, et al., 2022; Mateus et al., 2021; Mateus, Grifoni, Tarke, et al., 2020; Meckiff et al., 2020; Mele et al., 2021; Melo‐Gonzalez et al., 2021; Murugesan et al., 2021; Nelson et al., 2022; Ogbe et al., 2021; Painter et al., 2021; Paul et al., 2022; Peluso et al., 2022; Perez‐Gomez et al., 2022...…”
Section: Introductionmentioning
confidence: 99%
“…When blood samples from 37 patients who were hospitalized in the acute phase of COVID-19 were analyzed around 2 weeks after symptoms onset, the number of both spike (S) protein- and nucleocapsid (N)-specific CD4 + T cells with polyfunctionality (IL-2 + TNF-α + and IL-2 + IFN-γ + ) in patients with mild disease was higher than that in patients with severe infection. S-specific polyfunctional CD8 + T cells were also higher in patients with mild disease than in those with severe disease [ 24 ], whereas there is an apparent difference in the expression of coinhibitory molecules between patients with mild and severe diseases. S-specific CD8 + and CD4 + T cells in patients with severe disease express PD-1, TIM-3, CD39, VISTA, and Galectin-9 compared to those in patients with mild disease [ 25 ].…”
Section: Introductionmentioning
confidence: 99%